Improvement of Providing Therapeutic Dental Care to Pregnant Women. Therapeutic and Preventive Measures (Eurasian Research Bulletin, 2023)
Pregnancy is a critical period for dental health women [Zhulyov E. N., 2002; Fleisher G. M,2007; Chen J. P, 2000]. Pregnant women are at risk for the development and progression of major dental diseases - caries and periodontal diseases [Torchinov A. M., 2009; Zharkova O. V., 2008; Bitarova M. V., 2010; Yamschikova E. E., 2010; Maslak E.E., 2010; Gazizova R. N., 2014; Sharygin V. A., 2014; Alieva, 2016]. Long-term scientific studies prove that during pregnancy significantly increases the intensity and prevalence of dental caries [Bakhmudov M. B., 2010; Kiselnikova L.P., 2012]. During the physiological pregnancy, the prevalence of caries is up to 99%, and with pregnancy complicated by preeclampsia - up to 100% [Yamshchikova E. E., 2010]. The need for pregnant women in therapeutic care for caries and its complications is 94.7% [Bizyaev A.F., 2002; Yakubova I.I., 2007]. During pregnancy also significantly increases the rates of inflammatory periodontal diseases - gingivitis and periodontitis [Orekhova L. Yu., 2012; 2013]. Thus, numerous studies show a high the need of pregnant women in the sanitation of the oral cavity. This is all the more important that dental pathology of pregnant women affects the development of the fetus and in further affects the health of the child [Kuzmina E. M., Doroshina V. Yu., 1997; Voloshina I. M., 2013; Silk H., 2008]. In this regard, it is relevant to develop an algorithm for efficient and safe treatment of dental diseases in women on various pregnancy, which will help improve dental status of women and antenatal prevention of dental health children.